1-[6-Chloro-4-(2-chlorophenyl)-2-methyl-3-quinolyl]ethanone - Preeti, B.; Sarveswari, S.; Vijayakumar, V.; Tan, K.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title compound, C(18)H(13)Cl(2)NO, features an essentially planar quinoline ring system (r.m.s. deviation = 0.023 angstrom) with the acetyl [C-C-C-O torsion angle = -78.27 (17)degrees] and benzene [C-C-C-C torsion angle = 110.11 (14)degrees] substituents being twisted out of the plane; the dihedral angle formed between the mean planes of these two substituents is 58.01 (8)degrees. The acetyl O and benzene-bound Cl atoms lie to opposite sides of the molecule. Centrosymmetric aggregates mediated by pairs of C-H...O contacts are found in the crystal structure, and these are connected into a two-dimensional array in the ((1) over bar 01) plane via Cl...O [3.0508 (11) angstrom] interactions.